Health and social care professionals' views and experiences of supporting parents with serious mental illness - Oakes, Lucy; Wolfenden, Lauren; Drake, Richard J.; Calam, Rachel; Gregg, Lynsey (Frontiers in Psychiatry, 2023)
Introduction: A significant number of individuals with serious mental illness (SMI) such as schizophrenia or bipolar disorder are also parents of dependent children. Despite the risk of adverse psychological, behavioural, and social outcomes their needs often go unmet. To better understand the needs of parents with SMI and their children it is necessary to gain insight into the perspectives and experiences of the professionals in adult mental health and children's services who work with them, and who, ultimately, are best placed to meet those needs. Aims: To explore the views and experiences of health and social care professionals working with parents with SMI to understand the needs of, and their role supporting, parents with SMI and their children. Methods: Semi-structured interviews were conducted with seventeen professionals from six NHS and Local Authority settings in England, UK. Participants were included if they were employed in adult mental health or local authority children's' services and had experience of working with parents with SMI. Sampling was purposive, including a wide range of professions in these settings. Interview data were analysed using template analysis taking a critical realist perspective. Results: Three top-level themes were generated: (1) Impact of parental SMI on the child, (2) Accessing support from services, (3) Role of professionals working with parents with SMI. Themes highlight diverse, wide-ranging effects of SMI on the child and a reluctance from parents to seek help due to stigma and fear. Available services are reported to be inaccessible and unacceptable to parents with SMI and practitioners experience conflict when balancing the needs of the parent and child. A whole-family approach facilitated by improved communication between services is advocated. Conclusion: Participants believed that parents with SMI experience complex parenting challenges over and above other parents, describing a largely detrimental impact on the child. Support services were deemed inadequate, and participants stressed the need to develop specialist services tailored towards the needs of parents with SMI and their children. Although participants endorsed joined up working across health and social care settings to facilitate a whole family approach, they required greater service knowledge and training in parental SMI.